Impact of Opening Clauses on Bargained Wages - Wolf Dieter Heinbach (Institut für Angewandte Wirtschaftsforschung (IAW), 2005)
This paper is an analysis of the impact of different bargaining regimes on firm-specific wages and wage dispersion. In recent years, firms in Germany favored flexible to collective bargained wages. Opening clauses were introduced to combine collective bargaining and flexible adaptation of e.g. wages to firm-specific needs. An own survey evaluated whether central collective agreements contain these opening clauses. Then, the gathered information about opening clauses were linked to the Salary and Wage Structure Survey 2001. Focussing on central bargaining agreements, it has been tested whether bargained wages and wage dispersion differ under opened central bargaining coverage from that of non-opened central bargaining regimes. While wages with collective bargaining regimes tend to be higher, it could be found that wage dispersion under opened central collective bargaining coverage is slightly wider compared to non-opened central bargaining regime.
Keywords: J51; J31; 330; wages and wage dispersion; opening clauses; collective bargaining